Modeling and Control of the Locomotion of a Monopod Robot Mounted to a Vertical Slider - Xing, Siyuan; Kwan, Bradley Y.N.; Duan, Pengji (Journal of Vibration Testing and System Dynamics, 2026)
This paper studies the locomotion of a monopod robot mounted to a vertical slider. The robot is driven by two electric motors attached to its hip. Although the system is often used to develop and test low-level controllers of legged robots, its dynamics was only studied from the lumped model with massless legs. The actual system is more complex and interesting because it is over-actuated and single-degree-of-freedom during the stance phase but under-actuated and three-degree-of-freedom during the flight phase. In this paper, the equations of motion of the legged robot during stance and flight phases are established through the Euler-Lagrange method. The switching law governing phase transitions is derived based on the assumption of conversation of angular momentum. A phase-switching controller is proposed to stabilize dynamic gaits of the robot. Numerical simulations of the robot's locomotion with/without control are carried out through a Stateflow model. Results are validated through numerical simulations powered by Simscape Multibody. The effect of mass distribution of the hip and legs on jump height is discussed for optimized deign.